Is Cultural Change Necessary to Bring Gender Improvements to Agriculture? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Kate Raworth - Senior Researcher at OXFAM. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya